Modelling obesity outcomes: reducing obesity risk in adulthood may have greater impact than reducing obesity prevalence in childhood. Issue 7 (18th April 2013) - Lhachimi, S. K.; Nusselder, W. J.; Lobstein, T. J.; Smit, H. A.; Baili, P.; Bennett, K.; Kulik, M. C.; Jackson‐Leach, R.; Boshuizen, H. C.; Mackenbach, J. P.
Summary A common policy response to the rise in obesity prevalence is to undertake interventions in childhood, but it is an open question whether this is more effective than reducing the risk of becoming obese during adulthood. In this paper, we model the effect on health outcomes of (i) reducing the prevalence of obesity when entering adulthood; (ii) reducing the risk of becoming obese throughout adult life; and (iii) combinations of both approaches. We found that, while all approaches reduce the prevalence of chronic diseases and improve life expectancy, a given percentage reduction in obesity prevalence achieved during childhood had a smaller effect than the same percentage reduction in the risk of becoming obese applied throughout adulthood. A small increase in the probability of becoming obese during adulthood offsets a substantial reduction in prevalence of overweight/obesity achieved during childhood, with the gains from a 50% reduction in child obesity prevalence offset by a 10% increase in the probability of becoming obese in adulthood. We conclude that both policy approaches can improve the health profile throughout the life course of a cohort, but they are not equivalent, and a large reduction in child obesity prevalence may be reversed by a small increase in the risk of becoming overweight or obese in adulthood.